Implementation Of Entrepreneurship Strategies Based On Digital Marketing For Students' Micro Enterprises In The Surabaya Kemenkes Poltekkes Environment - Maghfiroh, Anita Mifthahul; Setiawan, Singgih Yudha; Wakidi, Levana Forra (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Entrepreneurship Development Program: Implementation of Digital Marketing-Based Entrepreneurship Strategies for Student Micro Enterprises in the Surabaya Ministry of Health Polytechnic Environment, motivated by the need to increase students' entrepreneurial competence in facing business competition in the digital era. Students who run micro businesses often do not utilize digital marketing strategies optimally. The aim of this program is to equip students with digital marketing skills so that their businesses can develop more effectively. The main contribution of this program is providing training, guidance and business capital to five selected MSMEs, so that students are able to implement digital-based marketing strategies independently. Methods for implementing activities include digital marketing workshops, submitting and selecting business proposals, as well as mentoring for MSMEs that pass the selection. Every MSME is given access and training in using digital platforms such as social media, e-commerce and other digital marketing tools. The program results show that the student MSMEs involved were able to optimize the marketing of their products and services through digital platforms, such as Instagram, YouTube and Shopee. Apart from that, five MSMEs that passed the proposal selection received business capital support and succeeded in increasing visibility and sales through the digital marketing strategy implemented. In conclusion, this program succeeded in increasing students' capacity to manage micro businesses in a more professional and competitive manner. The implication is that the development of digital-based entrepreneurship has the potential to accelerate the growth of student MSMEs and contribute to improving the local economy in the campus environment.